Covalent immobilization of laccase in green coconut fiber and use in clarification of apple juice. Issue 3 (March 2015) - Bezerra, Thaís Milena de Souza; Bassan, Juliana Cristina; Santos, Victor Tabosa de Oliveira; Ferraz, André; Monti, Rubens
Graphical abstract